Acknowledging Student Behavior: A Review of Methods Promoting Positive and Constructive Feedback. (August 2020) - Whitney, Todd; Ackerman, Kera B.
Positive and constructive feedback is a form of positive reinforcement essential to effective instruction and classroom management. This article provides practitioners with a range of realistic positive and constructive feedback strategies and descriptions of how such feedback can be implemented in schools and classrooms, with a special focus on the reinforcement of students with emotional and behavioral disorders.